Cactus kirigami for efficient fog harvesting: simplifying a 3D cactus into 2D paper art. Issue 27 (11th May 2020) - Bai, Haoyu; Zhao, Tianhong; Wang, Xinsheng; Wu, Yuchen; Li, Kan; Yu, Cunming; Jiang, Lei; Cao, Moyuan
Abstract : By simplifying a 3D cactus into 2D paper art, a cactus kirigami is proposed for efficient but inexpensive fog collection. The unique functions of cacti are completely mimicked, including droplet self-propulsion and interface refreshing. Abstract : Harvesting atmospheric water is a promising method for solving the water crisis in undeveloped regions, possessing remarkable advantages such as the use of simple structures, energy independence, low cost, etc. Cactus spines with a conical shape are able to achieve efficient water harvesting, but the fabrication of such a three-dimensional structure is complicated and tedious. Here we simplify cactus-inspired fog collecting spines from a 3D cone to a 2D triangle by designing a cactus kirigami. The wax-infused kirigami with anisotropic shape can reproduce the function of cactus spines, i.e., the efficient capture of fog droplets and rapid refreshing of the collecting interface through directional droplet self-propulsion. Fluid simulations suggest that the thinner spine with a small apex angle gives a higher onward flow speed for better fog capture. On the basis of the promising functions and the simplified structure, the cactus kirigami can be scaled up. Under a fog flow of ∼220 cm s −1, the water harvesting rate of cactus kirigami can reach ∼4000 mg cm −2 h −1, which is 1.6 and 11 times the rates of harp-like and plate collectors, respectively. Furthermore, the cost of this paper-based substrate and the construction process is largely reduced to nearly 0.5 per m 2 . This work provides a rational design for advanced fog harvesters, and should unlock more possibilities to develop functional materials from 3D to 2D for microfluidics, condensation, liquid collection, etc.